2013
DOI: 10.1111/ecoj.12014
|View full text |Cite
|
Sign up to set email alerts
|

Deficits, Public Debt Dynamics and Tax and Spending Multipliers

Abstract: Cutting government spending can increase the budget deficit at zero interest rates according to a standard New Keynesian model, calibrated with Bayesian methods. Similarly, increasing sales taxes can increase the budget deficit rather than reducing it. Both results suggest limitations of 'austerity measures'. At zero interest rates, running budget deficits can be either expansionary or contractionary depending on how they interact with expectations about long-run taxes and spending. The effect of fiscal policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The elasticity of substitution between intermediate goods is set to θ = 6, which yields a markup of 20%. This value is consistent with the estimates of existing studies such as Broda and Weinstein (2006), which report that the median value of θ ranges from 3 to 4.3, while Denes et al (2013) estimate θ to be approximately 13. The price adjustment cost is set to ψ = 400, a calibration that lies between the estimates of Ireland (2003) and Boneva et al (2016) of 162 and 495 for the parameter, respectively.…”
Section: Calibrationsupporting
confidence: 91%
“…The elasticity of substitution between intermediate goods is set to θ = 6, which yields a markup of 20%. This value is consistent with the estimates of existing studies such as Broda and Weinstein (2006), which report that the median value of θ ranges from 3 to 4.3, while Denes et al (2013) estimate θ to be approximately 13. The price adjustment cost is set to ψ = 400, a calibration that lies between the estimates of Ireland (2003) and Boneva et al (2016) of 162 and 495 for the parameter, respectively.…”
Section: Calibrationsupporting
confidence: 91%
“…We set the ratio of government spending to total output in the deterministic steady state equal to 0.2. The labor income tax rate is set to 0.3 and the consumption tax rate to 0.1, as in Denes, Eggertsson, and Gilbukh (2013). In the baseline, the steady state government debt to annualized output ratio is set to 0.5 but we also consider lower and higher values in the sensitivity analysis.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…A rather weak causal effect, however, was observed from inflation to budget deficit. Deficits, public debt dynamics, tax and spending multipliers examined by Denes, Eggertsson, and Gilbukh (2012) showed that increased sales taxes increases the budget deficit rather than reduce it. In effect, fiscal policy action is hugely dependent on the government policy regime.…”
Section: Literature Reviewmentioning
confidence: 99%